Tensile Behavior of Hybrid Fiber-Reinforced Ultra-High-Performance Concrete - Li, Jiayue; Deng, Zongcai (Frontiers in Materials, 2021)
30 dog-bone-shaped specimens were tested to study the effects of steel fiber mixed with seven kinds of non-metallic fibers on the tensile properties of ultra-high performance concrete (UHPC). Through experiments and micromorphological analysis, the effects of hybrid fibers on the compressive strength, tensile strength, peak strain, fracture energy, and characteristic length of UHPC were analyzed. The results showed that the hybrid fiber reinforced UHPC showed good ductile failure characteristics, which reflected the good crack resistance and toughening effect of different fibers; The tensile stress-strain curves of UHPC with different hybrid fibers can be divided into two parts: ascending section and softening section, and the softening section was greatly affected by the type and content of fibers; Basalt fiber with a diameter of 0.02 mm had the most obvious strengthening effect on UHPC, and polyvinyl alcohol fiber with a diameter of 0.2 mm and length of 8 mm had the best toughening effect; The mixing of steel fiber and non-metallic fiber can not only reduce the preparation cost but also improve the fracture energy and toughness of UHPC.